2003
DOI: 10.1080/713609356
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Cardiac Arrhythmias: DADs, EADs, and Alternans

Abstract: Rapid progress has been made in understanding the molecular mechanisms by which calcium ions mediate certain cardiac arrhythmias. Principal advances include imaging of cytosolic calcium in isolated cells and in intact tissues, use of fluorescent indicators and monophasic action potentials to record membrane potentials in isolated tissue, and sequencing of the genes that encode critical ion channel proteins. In this review, five types of arrhythmias are discussed where calcium ion currents, or currents controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 85 publications
2
74
0
6
Order By: Relevance
“…Although primarily used clinically for supraventricular arrhythmias, verapamil is also known to prevent VF caused by ischemia in patients with coronary artery disease and may reduce ventricular tachyarrhythmias associated with I/R. 24,25 As expected, verapamil treatment significantly reduced I/R-induced ventricular tachyarrhythmia and reduced the incidence of VF after MI. These data suggest a role for altered Ca 2ϩ handling in the increased cardiac arrhythmia in nNOS Ϫ/Ϫ mice after MI.…”
Section: Ventricular Arrhythmia In Nnosmentioning
confidence: 67%
“…Although primarily used clinically for supraventricular arrhythmias, verapamil is also known to prevent VF caused by ischemia in patients with coronary artery disease and may reduce ventricular tachyarrhythmias associated with I/R. 24,25 As expected, verapamil treatment significantly reduced I/R-induced ventricular tachyarrhythmia and reduced the incidence of VF after MI. These data suggest a role for altered Ca 2ϩ handling in the increased cardiac arrhythmia in nNOS Ϫ/Ϫ mice after MI.…”
Section: Ventricular Arrhythmia In Nnosmentioning
confidence: 67%
“…In addition, the prolonged phase of Ca 2+ release that gives rise to EADs helps to unload Ca 2+ from the SR, preventing SR overfilling. The ionic mechanisms of EADs are diverse and can involve Ca 2+ -dependent and Ca 2+ -independent processes (23,24). Because Ca 2+ release is decreased in RyR2-A4860G +/− cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that 5-HD, a specific inhibitor of mitochondrial K ATP channels could abo- lish the anti-arrhythmic effect of Ex-4, indicating that mitochondrial K ATP channels may be involved in the anti-arrhythmic effect of Ex-4. Many studies showed that activation of mitochondrial K ATP channels could limit mitochondrial Ca 2+ overload and maintain mitochondrial Ca 2+ homeostasis during MI [16,17]; mitochondrial Ca 2+ homeostasis plays a fundamental role in cytosolic free Ca 2+ homeostasis and could prevent ischemia-induced cytosolic free Ca 2+ overload [18,19] which plays an important role in ischemia-induced ventricular arrhythmias [20]. Thus, mitochondrial K ATP channels was involved in the anti-arrhythmic effect of Ex-4 during MI.…”
Section: Discussionmentioning
confidence: 99%